PENGARUH ARUS KAS OPERASI TERHADAP PERUBAHAN DIVIDEN DENGAN AKRUAL SEBAGAI VARIABEL MODERATING - Meythi , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
This research is aimed to examine and find out empirical evidence of the influence cash flows from operations on dividend changes with accrual as the moderating variable. The contributions of this study are twofold. First, suggesting the investors to use cash flows from operations when the predict dividend yield or dividend changes. Second, enriching literature on financial field.The hypothesis was tested by multiple regressions analysis for 30 firm on Indonesian Stocks Exchange (IDX) for period 1999 until 2005 with 95% confidence interval. The data are collected using purposive sampling method. The association between cashflows from operations and dividend changes are measured by Lintner's autoregresive dividend policy model (1956). The dividend changes are measured by using Firm-Specific Coefficients Methodology (FSCli, 0. This study provides evidence that accrual hasn't impact on the association between cash flows from operations and dividend changes. Thus, thehypothesis ofthe research is not empirically supported.Keywords: Cash Flows from Operations, Dividend Changes, andAccrual